RELATIONSHIP BETWEEN PAIN INTENSITY WITH SLEEP QUALITY OF PATIENT POST CAESAREAN SECTION IN RS TK. II DUSTIRA CIMAHI YEAR 2017 - Hevy Amelia Noviyanti; Eny Kusmiran; Marlin Sutrisna (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2019)
ABSTRACT Background. Cesarean section is an artificial birth, in which the fetus is born through an incision in the abdominal wall and uterine wall and the weight of the fetus is above 500 grams. Impacts that occur after caesarean section are pain and sleep disorders. Aim. To know the relation of pain intensity with sleep quality of mothers post cesarean section. Research methods. Using cross sectional approach. The sample of the study were 42 post-cesarean mothers taken by accidental sampling technique. The data was collected at RS TK. II Dustira Cimahi using Maternal Pain Questionnaire (MPQ) questionnaire for pain intensity measurement and The Sleep Sleep Quality Index (PSQI) for sleep quality measurement, in May 2017. Data analysis using Chi-Square test . Results. The highest intensity of pain occurred in the client after cesarean section with severe pain intensity with 22 respondents (52,4%) and uncomfortable there were 20 respondents (47,6%) and more than most client experience poor sleep quality that is 28 respondents ( 66.7%) but there are still clients who experienced good sleep quality 14 respondents (33.3%). The statistical test results obtained p significance number p = 0,000 thus p <α (0.000 <0.05), then H0 is rejected. Conclusion. There was a significant relationship between the intensity of pain and sleep quality in post-caesarean section patients. Keywords: Cesarean Section, Pain, Sleep Quality